Review Paper on Affective and Cognitive factors that affect banking Relationship with respect to Millennial - Chauhan, Rahul; Patel, Neerav (Journal of Advances in Accounting, Economics, and Management, 2024)
The aim of this paper is to explore the affective and cognitive factors that condition banking relationships for economically vulnerable consumers and how these factors contribute to increasing financial difficulties and exclusion. This research, performed on a set of focus groups, bases its findings on a combination of experimental and discourse analysis methods. Financial decisions are not rational and can be biased by affective and cognitive factors. Behavioural finance has focused very little on analysing how consumer biases influence relationships with banking institutions. Additionally, these relationships are affected by the digitalization and transformation of banking business. Thus, in the case of economically vulnerable consumers, who are not profitable for the increasingly competitive banking industry and lack financial abilities, their risk of financial exclusion is increasing. The results show that distrust and shame lead to financial difficulties in economically vulnerable consumers. Distrust generates problems of access and self-exclusion, while shame generates difficulties of use. This lack of trust makes them more rational when dealing with machines than with people, showing greater banking difficulties for consumers with a “person-suspicious” profile. This finding can help regulators establish limits on banking behaviour, require banks to incorporate affective and cognitive factors in their convenience tests and detect new variables that can help them improve their insolvency ratios and reputations. Discourse Analysis, Behavioural Finance, Financial Exclusion, Vulnerable Consumers, Affectivecognitive Factors